Dispersal of taeniid eggs: Experimental faecal contamination of forest environment followed by DNA detection in wild berries - Sanna Malkamäki; Antti Oksanen; Anu Näreaho; Antti Sukura (Food and Waterborne Parasitology, 2022)
To understand Taeniidae epidemiology, the principles of egg-dispersion dynamics under natural conditions must be known. In this study, non-zoonotic Taenia laticollis was used as a model parasite for the family Taeniidae (including Echinococcus spp.). An experiment to investigate dispersion from contaminated faeces to the surroundings was performed both with bilberries (Vaccinium myrtillus) and lingonberries (Vaccinium vitis-idaea), both of which are commercially harvested wild berries in Finland. For this experiment, 30 g of fox faeces was inoculated with 30,000 T. laticollis eggs for the bilberry experiment and 100,000 eggs for the lingonberry experiment. The faecal material was placed in the middle of good berry growth areas in four locations for bilberries and eight locations for lingonberries. After 41–42 days, berries at different distances (0–15 m) from the original contamination spot were collected and delivered to our laboratory. DNA was extracted from washed and sieved material and analysed using T. laticollis-specific semi-quantitative SYBR Green real-time polymerase chain reaction (qPCR). Taenia laticollis-specific DNA was recovered from 67% (8/12) of bilberry samples but not reliably from any of the lingonberry samples 0% (0/24), although the exposure dose was higher for those. The qPCR results suggest that under natural conditions, taeniid egg dispersion from the contamination spot is demonstrated but attachment is berry specific. The surface of bilberries may be more adhesive for taeniid eggs than the waxier and harder pericarp of the lingonberries or there might be a difference in the dispersal mechanism caused by different biotopes.